Tokoh-Tokoh Pendidikan Islam Dan Latar Belakang Kelas Sosiologis - Rahma Niadini (LPPM IAIN Sorong, 2022)
Educations is guidance, leadrship,from educators to students with phsyical and spritual development, educations shapes the character, nature, and, behavior of student systematically. Educations is a development of students to develop the potential, reason. And abilities possessed by students. In educations have several figures in the science of educations. The purpose of writing is to describe the Islamic education figures and the sociologicalclass background. The method used in this research is descriptive with collection techniques using library research or library research. The result of the literature study, the researcher described several examples of Islamic education and also the sociological class background. Sociology is the study of society or what we call the science of society. Sociology itself is a science that studies the relationship between humans in groups and their social structures. Education is a conscious and planned effort to realize and develop his potential to have spiritual strength, religion, self-control, personality, noble character and skills needed by himself, society, nation and state. Education in another sense is learning that is also accompanied by a process of changing the attitudes and behavior of a person or group in an effort to mature humans through teaching and training. Sociology of education is the study of society in the educational environment. Sociology of Islamic Education is the study of society in the Islamic education environment. Social class is a layer of individuals who each have the same position in a continuum of social status. (1) Islamic education figures (2)sociological class background.